MEMBONGKAR WACANA DISKRIMINASI GENDER DALAM PUISI MINAH TETAP DIPANCUNG KARYA DENNY JA: STUDI WACANA KRITIS - Insum Malawat (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The goals of this research is to take apart the meaning and writer’s ideology by “Minah Tetap Dipancung” poem. It do by seeing the relationship between the text and social context in critism paradigm. It focuses to object position, the point of subject view and how the text to perform writer and readers position. The result of this research is find biner position of characters in the poem. The readers position is to give the meaning, enjoyer, and writer helper to effort his ideology.